The Influence of Brand Equity, Quality, and Price on Consumer Satisfaction of Ades Brand Bottled Drinking Water in The Sekayu City Sub-District Community Musi Banyuasin District - Putri, Novi Dwi; Moelyati, Trisniarty Adjeng; Choiriyah, choriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine the effect of Brand Equity, Quality, and Price on Consumer Satisfaction of Ades Brand Bottled Drinking Water in the Community of Kota Sekayu District, Musi Banyuasin Regency. To find out the Effect of Brand Equity on Consumer Satisfaction with Ades Brand Bottled Drinking Water in the Community of Kota Sekayu District, Musi Banyuasin Regency. To find out the Effect of Quality on Consumer Satisfaction of Ades Bottled Drinking Water in the Community of Kota Sekayu District, Musi Banyuasin Regency. To find out the Effect of Price on Consumer Satisfaction of Ades Brand Bottled Drinking Water in the Community of Kota Sekayu District, Musi Banyuasin Regency. The samples used were 97. The sampling technique was by using a simple random sampling technique. This study uses a questionnaire to collect data and is supported by other methods to refine the information obtained. The data used are Primary Data and Secondary Data. The results showed that (1) there was a positive and significant influence between brand equity, quality, and price on consumer satisfaction of packaged drinking water with the Ades brand in the people of Kota Sekayu District, Musi Banyuasin Regency. (2) There is a positive and significant influence between brand equity and Ades brand bottled water consumer satisfaction in the people of Kota Sekayu District, Musi Banyuasin Regency. (3) There is a positive and significant relationship between the quality and consumer satisfaction of Ades bottled water in the Kota Sekayu District, Musi Banyuasin Regency community. (3) There is no significant effect between price and consumer satisfaction in packaged drinking water with the Ades brand in the people of Kota Sekayu District, Musi Banyuasin Regency.